Using of SVM for diagnosis of major depressive disorder - Ansari, Abdollah; Khalili, Mehdi (Journal of Advanced Computer Science & Technology, 2015)
artificial neural networks are used extensively in diagnosis are used and the system is able to detect a variety of conditions used in this study for diagnosis of major depressive disorder, 45 parameters were considered Implementation and operation using SVM model the use of different network error checked Education.